Knowledge-intensive exports of CEE and developed nations – driven by foreign or domestic capital? - Bryl, Łukasz (International Entrepreneurship Review, 2018)
Knowledge-based economy became the prevailing paradigm of the nations’ development and thus their competitive advantage foundations. Important role in the international recognition of country development is the growth of knowledge-intensive exports. Studies show that in the most developed nations high-tech exports plays crucial and rising role. As a result developing nations should maximize their efforts to increase exports of the knowledge-intensive products to follow the pattern of developed countries. However, growth of high-tech exports is often driven not by domestic resources but by foreign capital. The aim of the article is twofold. First, to present the growth of high-tech exports in CEE countries in comparison to developed countries. Second, to analyze what is the involvement of foreign capital in high-tech exports with the sub-industry breakdown. To perform a study research sample consisting of total 14 nations was formed. Analysis referred to the 2007-2015 years. Data derived from the Eurostat database (NACE Rev. 2 as high-tech industry classification).